69.2k views
4 votes
Use what you have learned to solve the following polynomial equation by either completing the square or using the quadratic formula.

(x^2-4x-6)(4x^2-8x-2)=0

Write your answer in radical form and as a decimal.
Then, write the equation in factored form and find the zeros of the graph of the

1 Answer

3 votes
(x^2-4x-6) factors into:
(x -5.1623) (x+1.1623)
Therefore x = 5.1623 and x = -1.1623

(4x^2-8x-2) factors into:
(x -2.2247) * (x +2.2474)

Therefore x = 2.2247 and x= -0.22474


User Pajdziu
by
5.9k points